Inhibition of malignant cells by silver anodes in vitro (Annals of Medical Research, 2021)
Aim: The aim of this study was to investigate the antitumoral effect of silver anodes.Materials and Methods: Pure silver electrodes and sham electrodes were placed in Petri dishes. Hep-II cells in culture media were added. The electrodes were connected with a direct current source. After incubation, the cells were examined and counted under an inverted microscope.Results: With an applied current of 4.0 µA, a clear inhibition zone was seen around the anode but not around the cathode. There was no inhibition zone around the anode or cathode with a 1.0 µA applied current or around the sham electrode.Conclusion: Metallic silver alone is not capable of inhibiting malignant cell growth, but our findings demonstrated an antitumoral effect of silver anodes in vitro. This effect was both current- and silver ion-dependent. Throughout the experiment, the electrical charges were acceptable in that they do not have harmful effects on normal living and undifferentiated human cells. Further studies are needed to evaluate clinical applications.